FRI0454 Endothelial Dysfunction in Psoriatic Arthritis: Evaluation by Endothelial-Dependent Flow-Mediated Dilation and Coronary Flow Reserve. (15th July 2016) - Murdaca, G.; Bezante, G.; Penza, E.; Balbi, M.; Negrini, S.; Puppo, F.
Abstract : Background: Patients with psoriatic arthritis (PsA) are at an increased risk for premature cardiovascular disease (CVD) independent of traditional risk factors [1]. Endothelial dysfunction plays a central role in the development of accelerated atherosclerosis. Objectives: To evaluate endothelial dysfunction by assessment of artery endothelial-dependent flow-mediated dilation (FMD) and coronary flow reserve (CFR). Methods: 20 patients (12 males and 8 females – age 57, 5 ±10, 8 years) affected by PsA according to CASPAR criteria [2] were enrolled. The 10-years cardiovascular Framigham risk score was calculated. Ultrasound assessment of brachial artery FMD was performed according to Corretti et al. [3]. CFR was evaluated by contrast-enhanced Doppler echocardiography and dipyridamole administration as previously described [4]. Results: The 10-years cardiovascular Framingham risk score of PsA patients (mean 3.84 ± 3.22) was in the low risk range. The assessment of brachial artery FMD showed a significant reduction of post-ischemic vasodilation in PsA patients (mean -17.70 ± 16%) as compared with normal population (mean +15.00 ± 5%). Coronary flow reserve was under the normal range (CFR >2.5) [5] in 15/20 PsA patients. Conclusions: The present results demonstrate that PsA patients with low cardiovascular Framingham risk score have increased arterial stiffness and decreased coronary arteries flow reserve. These data suggest that endothelial dysfunction may underlie premature atherosclerosis in PsA patients References: Ogdie A et al., Ann Rheum Dis 2015; 74: 326–32. Taylor W et al., Arthritis Rheum 2006; 54: 2665–73. Corretti MC et al., J Am Coll Cardiol 2002; 39: 257–6. Sulli A et al., Rheumatology 2004; 43: 505–9. Caiati C et al., Circulation 1999; 99: 771–8. Acknowledgement: This work is supported by Pfizer Disclosure of Interest: None declared